KEPEMIMPINAN ALTRUIS DALAM MEMBENTUK ORGANIZATIONAL CITIZENSHIP BEHAVIOUR PADA PEGAWAI DI SMP PLUS NURUL HIKMAH PAMEKASAN - Iswatun Hasanah; Hilmi Qosim Mubah (re-JIEM (Research Journal of Islamic Education Management), 2022)
This study aims to understand how altruistic leadership can lead to Organizational Citizenship Behavior (OCB) behavior in employees at the SMP Plus Nurul Hikmah Pamekasan Institute. Using field research with a case study approach with three stages, namely field preparation, research stage, and post-stage. Data collection techniques used comprehensive research guidelines, non-participatory observation, and study documentation. The subjects of the study were the principal and three teachers of SMP Plus Nurul Hikmah Pamekasan who were male and showed positive performance and were indicated to have OCB and high loyalty to the institution. Miles and Huberman's data analysis model is used interactively and intensively to obtain saturated data, which consists of data collection, data reduction, and data collection and leveraging. The results of the study indicate that this altruist leadership plays an important role in shaping Organizational Citizenship Behavior. Altruistic behavior can encourage the leader's capacity to grow and become a tool to influence subordinates toward collective goals, encourage happiness in the workplace, can encourage employee performance in organizations, increase organizational capabilities, and be able to improve subordinate innovation behavior.